2014
DOI: 10.1128/jvi.01053-14
|View full text |Cite
|
Sign up to set email alerts
|

Triggering TLR2, -3, -4, -5, and -8 Reinforces the Restrictive Nature of M1- and M2-Polarized Macrophages to HIV

Abstract: Macrophages must react to a large number of pathogens and their effects. In chronic HIV infection, the microenvironment changes with an influx of microbial products that trigger Toll-like receptors (TLRs). That dynamic nature can be replicated ex vivo by the proinflammatory (M1-polarized) and alternatively activated (M2-polarized) macrophages. Thus, we determined how polarized macrophages primed by various TLR agonists support HIV replication. Triggering of TLR2, -3, -4, -5, and -8 reinforced the low level of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 36 publications
5
40
0
1
Order By: Relevance
“…There is evidence that polarized macrophages of both phenotypes, are less susceptible to infection than resting monocytes and macrophages (14). Others have suggested that early in infection M1 macrophage are permissive to infection, while the cytokine shift that occurs in late stage HIV results in a shift towards the M2 phenotype, which is resistant to infection (15).…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence that polarized macrophages of both phenotypes, are less susceptible to infection than resting monocytes and macrophages (14). Others have suggested that early in infection M1 macrophage are permissive to infection, while the cytokine shift that occurs in late stage HIV results in a shift towards the M2 phenotype, which is resistant to infection (15).…”
Section: Introductionmentioning
confidence: 99%
“…E. coli LPS has been suggested to interfere with HIV replication at multiple steps of the HIV replication cycle in macrophages including interference of efficient viral entry (Franchin et al, 2000; Herbein et al, 1995; Herbein and Varin, 2010; Mikulak et al, 2009; Verani et al, 1997; Verani et al, 2002) and a restriction after entry but before proviral integration (Devadas et al, 2010; Donninelli et al, 2016; Pushkarsky et al, 2001; Schlaepfer et al, 2014; Wang et al, 2011). Our data suggests that a step post-proviral integration and transcription are targeted in MDMs when infected with HIV in the presence of P. gingivalis .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, macrophages within many anatomical compartments are susceptible to direct infection by HIV-1 and this infection correlates with macrophage dysfunction including altered cytokine production, phagocytosis, pathogen killing and chemotaxis (Pugliese et al, 2005). HIV replication is dependent on the regulation of transcription factors, cytokines and anti-viral restriction factors associated with macrophage activation and the cytokine microenvironment (Cassetta et al, 2013; Cassol et al, 2009; Herbein and Varin, 2010; Koyanagi et al, 1988; Schlaepfer et al, 2014; Schuitemaker et al, 1994; Schuitemaker et al, 1992). However, it remains unclear to what extent these signals affect long term HIV pathogenesis or possibly HIV persistence.…”
Section: Introductionmentioning
confidence: 99%
“…37 Further, M2aMf switch to quiescent Mf in the absence of IL-4, and are reprogrammed to Mf with function to switch to M1Mf in response to TLR agonists. 43 Therefore, M2aMf exist for a relatively short time. 44 Conversely, M2bMf live longer 45 and do not require exogenous growth factors (e.g., IL-4), due to the autocrine production of CCL1, which is an essential chemokine for the maintenance of M2bMf properties.…”
Section: Ccl1mentioning
confidence: 99%